A “Working” System Model of Car Buyer Behavior - Farley, John U.; Howard, John A.; Lehmann, Donald R. (Management Science, 1976)
A four-equation “working version” system based on elements of a buyer behavior model was used to organize an analysis of a five-wave consumer panel tracking the introduction of a new brand of subcompact automobile. Parameters of endogenous model variables are remarkably stable over time, alternative brands, parameter estimation methods and specially-defined subgroups of the panel, while parameters of exogenous model variables vary systematically. The model behaves reasonably in a systems sense when tested with extreme values of endogenous and exogenous variables.